Krankenschwester mit einem kleinen Jungen sprechend - Bonnot, Paul W.
soziale Fragen;Gesundheit;Gesundheitspolitik;Gesundheitswesen;Spital;Krankenpflege soziale Fragen;Gesundheit;ärztlicher Beruf;arztähnlicher Beruf